Program Corporate Social Responsibility (Csr) dalam Pilar Astra Cerdas di Pt Astra Agro Lestari Tbk - Nelsa Nelsa; Intan Fazira; Arifa Nurhidayanti; Dian Nurfadila; Yulita Septi Ardaneshwari; Sabania Amrina Rosada; Nur Fadhilah Dwi Putri Zaenong; Devi Petonengan; Moh. Taqwa; Rahmawati Halim; Andi Maman; Askar Mayusa (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the implementation of the Corporate Social Responsibility (CSR) Program under the Astra Cerdas pillar at PT Astra Agro Lestari Tbk as a form of corporate social responsibility in the field of education. The study employs a descriptive qualitative method, with data collected through observation, documentation, and Focus Group Discussions (FGDs). The Astra Cerdas Program is implemented in the company’s Ring-1 area, which includes Gunungsari Village, Pakawa Village, Ako Village, Ngovi Village, and Pasangkayu Subdistrict. The research findings indicate that the implementation of the Astra Cerdas CSR program is not only focused on providing educational assistance but is also directed toward sustainable social development. The programs implemented include scholarships for high-achieving students and underprivileged families, capacity building for educators, the construction of educational facilities and infrastructure, the development of Adiwiyata Schools, the Love Pink program, and special education for the Bunggu indigenous community through tutoring and the Kejar Paket program. These programs have a positive impact on improving access to education, the quality of learning, environmental awareness, and community empowerment in the areas surrounding the company’s operations. The implementation of the Astra Cerdas program demonstrates that CSR can serve as a strategic tool in fostering harmonious relationships between the company and the community while supporting the development of high-quality human resources